Business Model sebagai Strategi bersaing untuk Pelaku Bisnis Pemula Studi kasus: Bisnis Hijab - Yunitasari Christanti; Abdullah Umar; Agung Hari Sasongko; Indira Tyas Widyastuti (Sekolah Tinggi Ilmu Ekonomi YPPI Rembang, 2018)
In this era has begun many emerging businesses with small and medium scale managed by beginners who notabene they have no experience in business. With the sophistication of technology and also easy access through social media, facilitate the beginners of this business do business activities. New business is starting to bloom now is a hijab business. In social media, many hijab merchants offer various hijab models. Already emerging also beginners businessmen who produce their own hijab and make their own labels. They are usually the mothers who have sewing skills then they develop by designing their own hijab model that is the trend now, and try to produce and market it with their own label. Since such businesses are already emerging, newbies must have a mature business plan to avoid being run over by their competitors. Business Model Canvas should be developed for business planning as well as SWOT Analysis to design the improvement business. This research uses qualitative method to know how big role Business Model Canvas for beginners business also SWOT analysis which role to make repair business. Keywords: Business beginners, Business Model Canvas, SWOT Analysis